2016
DOI: 10.1111/1752-1688.12445
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variations in Eastern U.S. Hydrology: Responses to Global Climate Variability

Abstract: Coastal ecosystems are dependent on terrestrial freshwater export which is affected by both climate trends and natural climate variability. However, the relative role of these factors is not clear. Here, both climate trends and internal climate variabilities at different time scales are related to variations in terrestrial freshwater export into the eastern United States (U.S.) coastal region. For the recent 35‐year period, the intensified hydro‐meteorological processes (annual precipitation or evapotranspirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 115 publications
1
16
0
1
Order By: Relevance
“…Because multiannual cycles (e.g., ENSO) and events (e.g., long-term drought) have the potential to influence precipitation over periods greater than a decade [38,49], we distinguished those sites with between 30 and 40 years of quality-checked record from those with between 20 and 30 years of quality-checked record.…”
Section: Interannual Trends In Annual Precipitation Winter Precipitamentioning
confidence: 99%
See 1 more Smart Citation
“…Because multiannual cycles (e.g., ENSO) and events (e.g., long-term drought) have the potential to influence precipitation over periods greater than a decade [38,49], we distinguished those sites with between 30 and 40 years of quality-checked record from those with between 20 and 30 years of quality-checked record.…”
Section: Interannual Trends In Annual Precipitation Winter Precipitamentioning
confidence: 99%
“…Research has indicated that climate and associated hydrologic processes (such as streamflow production) have already begun to change in some parts of the world, including significant downward trends in precipitation in parts of India [34] and New Zealand [35], as well as downward trends in dry-season streamflow and upward trends in peak streamflow in parts of the United States [36][37][38][39][40]. If temperate dry-summer climate zones are undergoing changes in climate variables-such as increased or decreased annual precipitation-these changes could already be causing shifts in ecological community composition and structure.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the AWC network is located less than 10 km from the coast, where climate is strongly influenced by Atlantic Ocean dynamics (B. I. Feng et al, 2016;Namias, 1967;Seager et al, 2012;Wettstein & Mearns, 2002). We find strong correlations with the temperature-sensitive network's EOF1 with local and cross basin Atlantic SSTs (Figure 4; Pearl et al, 2017).…”
Section: Discussionmentioning
confidence: 54%
“…Feng et al, 2016;Namias, 1967;Seager et al, 2012;Wettstein & Mearns, 2002). Feng et al, 2016;Namias, 1967;Seager et al, 2012;Wettstein & Mearns, 2002).…”
Section: Discussionunclassified
“…Given that the southeastern United States is predicted to experience increases in drought frequency and intensity (Ficklin et al 2015;Feng et al 2016), efforts may be needed to protect sensitive wetland-associated species like N. floridana. Mitigating or managing drought effects is difficult, since droughts often span large spatial and temporal scales, and are unpredictable in timing and severity (Bond et al 2008).…”
Section: Discussionmentioning
confidence: 99%